Underwater remote sensing: linking acoustic to habitats - Che Hasan, Rozaimi (2015)
Acoustic mapping has becoming one of important tools in benthic habitat mapping to study in details species distributions and their spatial extents. Seabed data collected by acoustic sensors that offer high spatial resolution dataset with full coverage brings new opportunity for ecologist to thoroughly investigate benthic habitats in marine environment. This study attempts to highlight how acoustic dataset can be potentially linked to specific habitats through analysis of depth and backscatter returns acquired by multibeam echo sounder (MBES) sonar system. To demonstrate this, the authors have used sample data collected around Pulau Agas, one of the islands of Pulau Sembilan, Perak. These areas are found to have corals that can survive in extreme conditions (high sedimentation with less light penetration). Acoustic data were collected using MBES model WASSP WMB-3250 on 17 March 2015. The system recorded water depth as the main data source while configured to be able to output intensity values (backscatter returns). Further processing of the bathymetry map was done to study in details the potential locations of coral reef habitats. This was completed by deriving secondary layers or seascape derivatives that able to provide some indicators of the complexity of the seafloor. Bathymetry map reveals interesting geomorphology characteristics around study area with depth up to 90 meters (Figure 1). Backscatter mosaic provides additional information in terms of distinguishing hard and soft sediment classes where this was not available in the bathymetry map. Depth and backscatter data extracted along 1.4 km profile showed that backscatter values were not directly correlated with depths (Figure 2). Deeper areas might have backscatter pattern similar to shallower water. It shows that both bathymetry and backscatter presented different information of the seafloor and might be useful for remote characterization of the sediment types. For the secondary derivative layers (Figures 3-5), broad scale Benthic Position Index (BPI) showed features that might be occupied by benthic habitats. These areas were mapped at high slope values and minimum depth (shallow water area). In terms of backscatter mosaic, these areas were located where intensity values were high that might be relating to hard surface such as reefs. The same comments made to the patterns in the terrain ruggedness and bathymetry slope. Potential areas occupied by benthic habitats can be described as high slope areas (e.g. reef features) and high ruggedness. The advantage of this technique as compared to manual sampling technique is the high spatial resolution of the maps that can be very useful for marine managers. For coral reef habitat maps, BPI can be used as proxy to explain the distribution of these habitats. The complexity of the seafloor represented by terrain ruggedness and bathymetry slope provide a useful indicator to investigate its distribution.